Old tech but not low tech: telephone-based treatment provision for substance use - Walton, Mary R.; Kang, Augustine W.; DelaCuesta, Courtney; Hoadley, Ariel; Martin, Rosemarie (Frontiers in Psychiatry, 2024)
The future of telemedicine for substance use treatment hangs by threads as the United States awaits approval of proposed regulations and laws to increase care access in light of the 2022 Centers for Medicare and Medicaid Services revisions allowing for audio-only care.Telemedicine improves patient care access and outcomes. Audio-only telemedicine can be an effective and viable modality for individuals without technology resources (devices, internet services, literacy), those with reduced telehealth service utilization (Black individuals, unstable housing, older, low-income, low education), and those living in rural locations. Studies suggest that telephone visits for buprenorphine treatment are well-accepted by patients and providers, making telephone visits essential in care access to reduce disparities. Telephone counseling for patients in substance use treatment is convenient, flexible, and empowering and can augment therapeutic alliances and treatment goals. Both providers and patients advocate for patientcentered hybrid care to include telephone-only treatment, which enhances service productivity and care access, reduces no-show rates, costs, and stigma, and is sustainable. Numerous solutions can expand technology access, proficiency, assimilation, and trust. Despite being "old" technology, the telephone remains an essential resource for substance use treatment.